Complement Coercion: The Joint Effects of Type and Typicality - Zarcone, Alessandra; McRae, Ken; Lenci, Alessandro; Padó, Sebastian (Frontiers in Psychology, 2017)
Complement coercion (begin a book → reading) involves a type clash between an event-selecting verb and an entity-denoting object, triggering a covert event (reading). Two main factors involved in complement coercion have been investigated: the semantic type of the object (event vs. entity), and the typicality of the covert event (the author began a book → writing). In previous research, reading times have been measured at the object. However, the influence of the typicality of the subject-object combination on processing an aspectual verb such as begin has not been studied. Using a self-paced reading study, we manipulated semantic type and subject-object typicality, exploiting German word order to measure reading times at the aspectual verb. These variables interacted at the target verb. We conclude that both type and typicality probabilistically guide expectations about upcoming input. These results are compatible with an expectation-based view of complement coercion and language comprehension more generally in which there is rapid interaction between what is typically viewed as linguistic knowledge, and what is typically viewed as domain general knowledge about how the world works.